Discovery of a diffuse optical line emitting halo in the core of the Centaurus cluster of galaxies: line emission outside the protection of the filaments. Issue 4 (22nd December 2018) - Hamer, S L; Fabian, A C; Russell, H R; Salomé, P; Combes, F; Olivares, V; Polles, F L; Edge, A C; Beckmann, R S
ABSTRACT: We present the discovery of diffuse optical line emission in the Centaurus cluster seen with the MUSE (Multi Unit Spectroscopic Explorer) integral field unit. The unparalleled sensitivity of MUSE allows us to detect the faint emission from these structures which extend well beyond the bounds of the previously known filaments. Diffuse structures (emission surrounding the filaments, a northern shell and an extended halo) are detected in many lines typical of the nebulae in cluster cores ([NII]λ6548and6583, [SII]λ6716and6731, [OI]λ6300, [OIII]λ4959and5007, etc.), but are more than an order of magnitude fainter than the filaments, with the faint halo only detected through the brightest line in the spectrum ([NII]λ6583 ). These structures are shown to be kinematically distinct from the stars in the central galaxy and have different physical and excitation states to the filaments. Possible origins are discussed for each structure in turn and we conclude that shocks and/or pressure imbalances are resulting in gas dispersed throughout the cluster core, formed from either disrupted filaments or direct cooling, which is not confined to the bright filaments.